2018
DOI: 10.1111/pan.13333
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and factors contributing to postdischarge nausea and vomiting in pediatric ambulatory surgical cases

Abstract: We found an incidence of postdischarge nausea and vomiting of 14%. Intraoperative and postdischarge opioids increase the risk, with long-acting intraoperative opioids further accentuating the risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 27 publications
4
27
0
1
Order By: Relevance
“…Anesthesia-related risk factors ( Table 1 – Table 3 ) include the use of opioids, volatile agents, nitrous oxide (which increases the risk for postoperative vomiting), and high doses of neostigmine for the reversal of residual neuromuscular blockade 32 , 38 , 47 51 . General anesthesia is associated with a higher incidence of PONV compared with regional anesthesia 35 , 52 , 53 secondary to the greater requirement for opioid medication to control postoperative pain after general anesthesia in both adults and children 35 , 54 .…”
Section: Risk Factors For Ponv and Pdnvmentioning
confidence: 99%
“…Anesthesia-related risk factors ( Table 1 – Table 3 ) include the use of opioids, volatile agents, nitrous oxide (which increases the risk for postoperative vomiting), and high doses of neostigmine for the reversal of residual neuromuscular blockade 32 , 38 , 47 51 . General anesthesia is associated with a higher incidence of PONV compared with regional anesthesia 35 , 52 , 53 secondary to the greater requirement for opioid medication to control postoperative pain after general anesthesia in both adults and children 35 , 54 .…”
Section: Risk Factors For Ponv and Pdnvmentioning
confidence: 99%
“…However, their use is associated with a high risk of postoperative nausea and vomiting, as well as risks of urinary retention, respiratory depression, and delayed emergence from anesthesia. [16,17] Therefore, many studies have explored ketorolac, acetaminophen, and midazolam as alternatives to opioid to attenuate emergence agitation. [18] Some studies found that children premedicated with midazolam were less agitated after surgery while others reported that airway sensitivity to midazolam delayed discharge from the recovery room.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of PDNV in our study (32.9%) was higher than the 14.1% rate reported in another paediatric study. 3 This increased incidence may be explained by differences in patient selection and the criteria used for PDNV. Efune and colleagues 3 studied a cohort of patients and did not measure the severity of nausea, but recorded the parent's response to the question about nausea.…”
Section: Discussionmentioning
confidence: 99%
“…20 We planned to obtain data on 19 subjects with emesis to allow for missing data because of emergence delirium, delayed recovery, lack of cooperation from pain-related behaviours, or for other reasons. Assuming the incidence of emesis in the PACU was 10% in subjects receiving current standard perioperative care, 3…”
Section: Sample Sizementioning
confidence: 99%